The potential of Beauveria bassiana vuill to control rice leaf roller cnaphalocrocis medinalis guenee. Issue 1 (March 2021) - Abdullah, T; Kuswinanti, T; Aminah, S N; Asman, Asman
Abstract: The pest presence and environmental condition is very important factor on agricultural production especially manage rice growth in wetland. The purpose of the research is to study the role of Beauveria bassiana Vuill as entomopathogenic fungi against rice leaf roller Cnaphalochrosis medinalis Guenee (Lepidoptera: Pyralidae) in wetland rice field. Experimental research was held in Pest Laboratory, Plant Pests and Diseases Department, Faculty of Agriculture Hasanuddin University in March to August 2018. The source of C. medinalis larval from rice field in Moncongloe Bulu village, Maros district, South Sulawesi. B. bassiana isolate from Disease Laboratory collection in applied concentration 106 cfu to all of the treatment. The result showed in five days after applied B. bassiana the effective treatment control is P4 = C. medinalis sprayed and dipped rice leaves as food of larvae (100%) then P3 = dipped rice leaves into B. bassiana (90%); P2 = sprayed B. bassiana to body of C. medinalis larval (50%) and P1 = control (30%), respectively. The total mortality of C. medinalis after application B. bassiana started at five days in P4, faster than another treatment. The result of research, B. bassiana is very useful and safety manage population of C. medinalis in rice field.